Decolorization of selected azo dye by Lysinibacillus fusiformis W1B6: Biodegradation optimization, isotherm, and kinetic study biosorption mechanism - Sari, Ira Puspita; Simarani, Khanom (SAGE Publications, 2019)
This study reports on the evaluation of biodegradation and biosorption mechanism of indigenous bacteria on azo dye decolorization. The bacterial strains were screened for their ability in decolorizing of selected toxic azo dyes in aqueous solution. Lysinibacillus fusiformis W1B6 showed the highest decolorizing of about 96% of methyl red within 2 h, with the specific growth rate of 0.273/h. The optimum decolorization under aerobic condition was achieved at pH 7.5, 30 ± 2°C, inoculum 10% (v/v), and initial dye concentration of 100 mg/L. Spectrum analysis confirmed biodegradation as the principal mechanism of decolorization, although biosorption also occurred. Extracellular and intracellular azoreductase, laccase, and lignin peroxidase plays a role in the oxidoreductive mechanism of decolorization. The absorption isotherms fitted with the Langmuir equation and the reaction kinetics of methyl red decolorization followed a pseudo first-order. © The Author(s) 2019.